2022
DOI: 10.55420/2693.9193.v11.n2.39
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Connectedness in Online, Blended, and Face-to-Face Research Methods Courses among Hispanic and Low-Income Students

Abstract: When students feel connected to the instructor, they are more likely to remain motivated, engaged, and persist toward completing an online course. Rarely have studies compared connectedness in three modalities: online only, blended, and face-to-face. This study compared perceptions of connectedness among students (N = 27) from an Hispanic Serving Institution with their instructor and peers in a research methods course. The sample of students took the same course in three different sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Most of the studies conducted on this topic occurred in the state of California, which has many HSIs and large Hispanic population. In a novel study of a research methods course comparing students' grades in a synchronous face-to-face synchronous course, an online asynchronous course, and blended face-to-face synchronous and online asynchronous course, Latino students' grades were the lowest in the asynchronous online only course (Linton et al, 2021). Kraupp (2012) found that, Latino students receiving online asynchronous instruction at the California Community College System experienced a nine-percentage point lower success rate, grades that averaged two-tenths of a grade point lower, and withdrawal rates over twice as high as compared to Latino students in face-to-face synchronous sections.…”
Section: Teaching Modalities and Hispanic Student Outcomesmentioning
confidence: 99%
“…Most of the studies conducted on this topic occurred in the state of California, which has many HSIs and large Hispanic population. In a novel study of a research methods course comparing students' grades in a synchronous face-to-face synchronous course, an online asynchronous course, and blended face-to-face synchronous and online asynchronous course, Latino students' grades were the lowest in the asynchronous online only course (Linton et al, 2021). Kraupp (2012) found that, Latino students receiving online asynchronous instruction at the California Community College System experienced a nine-percentage point lower success rate, grades that averaged two-tenths of a grade point lower, and withdrawal rates over twice as high as compared to Latino students in face-to-face synchronous sections.…”
Section: Teaching Modalities and Hispanic Student Outcomesmentioning
confidence: 99%